Association of matrix metalloproteinases and adhesive molecules with important aspects of carotid artery stenosis - Ružanović, Ana (Journal of Medical Biochemistry, 2025)
Background: As symptom risk assessment in carotid artery stenosis (CAS) could be improved by parameters that reflect additional risk aspects such as chronic inflammation rate, and atherosclerotic activity on a systemic level, we investigated the association of serum matrix metalloproteinases-2,7,9 (MMP-2,7,9), vascular cell adhesion molecule-1 (VCAM-1) and selectins-P and E with symptomatic status, stenosis degree and plaque morphology in CAS patients in order to select parameters that associate to important clinical determinants of the symptom development risk.Methods: The study included 119 CAS patients and 46 healthy subjects. Carotid arteries were examined by color flow Doppler and B-mode Duplex ultrasound. Serum parameters were assessed using commercially available enzyme-linked immunosorbent assays (ELISA). Difference was tested by Mann-Whitney U, Kruskal-Wallis and Chi-square tests, and Spearman’s correlation was tested.Results: MMP-7 and selectin-P levels were higher in CAS than in controls (p